We start with the equation:
\[ \frac{x^{\frac{5}{3}}}{x^{\frac{6}{5}}} = x^a \]
To simplify the left-hand side, we use the property of exponents that states \(\frac{x^m}{x^n} = x^{m-n}\). Accordingly, we can write:
\[ \frac{x^{\frac{5}{3}}}{x^{\frac{6}{5}}} = x^{\frac{5}{3} - \frac{6}{5}} \]
Next, we need to find a common denominator to subtract the exponents. The denominators are 3 and 5. The least common multiple (LCM) of 3 and 5 is 15.
Now we can rewrite each fraction:
\[ \frac{5}{3} = \frac{5 \times 5}{3 \times 5} = \frac{25}{15} \] \[ \frac{6}{5} = \frac{6 \times 3}{5 \times 3} = \frac{18}{15} \]
Now we can perform the subtraction:
\[ \frac{5}{3} - \frac{6}{5} = \frac{25}{15} - \frac{18}{15} = \frac{25 - 18}{15} = \frac{7}{15} \]
Thus, we have:
\[ \frac{x^{\frac{5}{3}}}{x^{\frac{6}{5}}} = x^{\frac{7}{15}} \]
Now we can equate this to the right-hand side of the original equation:
\[ x^{\frac{7}{15}} = x^a \]
Since the bases \(x\) are the same, we can equate the exponents:
\[ \frac{7}{15} = a \]
Therefore, the final value of \(a\) in simplest form is:
\[ \boxed{\frac{7}{15}} \]